Real Time - "Mellor, D.H." (Cambridge, 1981)
This is a study of the nature of time. In it, redeploying an argument first presented by McTaggart, the author argues that although time itself is real, tense is not. He accounts for the appearance of the reality of tense - our sense of the passage of time, and the fact that our experience occurs in the present - by showing how time is indispensable as a condition of action. Time itself is further analysed, and Dr Mellor gives answers to most of the metaphysical questions it provokes, concerning the relation of time to space, the dissection of time, and its relation to change and causation.
Keywords: Time